2005
DOI: 10.1111/j.1745-4522.2005.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDATIVE FLAVONOIDS FROM THE FLOWER OF INULA BRITANNICA

Abstract: Eight flavonoids were identified from the flowers of Inula britannica var. chinensis as luteolin, diosmetin, chrysoeriol, kaempferol, quercetin, 6hydroxyluteolin-6-methyl ether, spinacetin and eupatin. Their structures were established by spectroscopic methods. All of the identified compounds exhibited considerable antioxidant activity in the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Diosmetin (2) showed a strong growth inhibitory effect against P-388 leukemia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Phenolic compounds possess various biofunctionalities including glucosidase and antioxidant activity (Liu et al, ), prevention of Alzheimer's disease (Nakajima et al, ), and neuroprotection (Liu et al, ). I. britannica is known to be a rich source of flavonols such as quercetin, kaempferol, luteolin, and patuletin (Bai et al, ; Kim et al, ), but epicatechin has not been previously found in I. britannica . Epicatechin is an isomer of catechin that possesses a cis ‐configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds possess various biofunctionalities including glucosidase and antioxidant activity (Liu et al, ), prevention of Alzheimer's disease (Nakajima et al, ), and neuroprotection (Liu et al, ). I. britannica is known to be a rich source of flavonols such as quercetin, kaempferol, luteolin, and patuletin (Bai et al, ; Kim et al, ), but epicatechin has not been previously found in I. britannica . Epicatechin is an isomer of catechin that possesses a cis ‐configuration.…”
Section: Discussionmentioning
confidence: 99%
“…[19 -21] The compounds, corresponding to the peaks 3, 5 -7, 12, 14, and 16 -27 ( Table 2) were isolated from the methanol extract of A. alba by column chromatography (CC) on Sephadex LH-20 and subsequent CC and PTLC of the obtained fractions (see Experimental Section). The identification of chlorogenic acid, [16] 3,5-and 4,5-dicaffeoylquinic acids, [16][17] [22] scopoletin, [18] [23] umbeliferone, [18] [23] luteolin, [24] [25] nepetin, [26] quercetin 3-methyl ether, [10] [27] axillarin, [10] [28] apigenin, [21] [25] hispidulin, [29] [30] diosmetin, [24][29] chrysoeriol, [24] [29] desmethoxycentaureidin, [30] jaceosidin, [31] quercetin 3,3 0 -dimethyl ether, [20] centaureidin, [10] [32] and rutin [25] was achieved by comparison of their 1 H-NMR, MS, and UV spectral data with those published in the literature and/or with authentic standards. Their structures are presented in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Inula, a variable perennial herb, is comprised of approximately 100 species worldwide that are distributed mainly in Asia, Europe, and Africa [11]. Many Inula species are used in traditional medicine for the treatment of bronchitis, diabetes, intestinal ulcers, digestive disorders, and inflammation in various parts of the world [12,13]. Among the species, the flowers of Inula britannica Linnaeus (Asteraceae) exhibit antibacterial, carminative, diuretic, and laxative properties [14], which are associated with the presence of various biologically active compounds, such as steroids, terpenoids (sesquiterpenes, diterpenes, and triterpenoids), phenolics, and flavonoids [15].…”
Section: Introductionmentioning
confidence: 99%